2020
DOI: 10.2147/ndt.s253337
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sensory Integration and Perceptual-Motor Profiles in School-Aged Children with Autistic Spectrum Disorder</p>

Abstract: Purpose This study aimed to investigate the sensory integration and perceptual-motor performances in elementary school children (5–12 years) with autistic spectrum disorder (ASD) in Taiwan. The impacts of comprehensive body functions on activity participations in ASD were also investigated to provide evidence for clinical applications and further study. Methods One hundred and seventeen children with ASD (42 females; aged 5–13 years, average age 8 years 3 months) were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…The sensory-related behavioral symptoms of our ASD sample are similar to the results of previous studies [ 31 , 48 , 49 ]. Furthermore, Purpura and collaborators [ 33 ] suggested the presence of early sensory-motor abnormalities in children with ASD and the link between sensory dysfunctions and motor abnormal behaviors in this population already during the preschool age.…”
Section: Discussionsupporting
confidence: 88%
“…The sensory-related behavioral symptoms of our ASD sample are similar to the results of previous studies [ 31 , 48 , 49 ]. Furthermore, Purpura and collaborators [ 33 ] suggested the presence of early sensory-motor abnormalities in children with ASD and the link between sensory dysfunctions and motor abnormal behaviors in this population already during the preschool age.…”
Section: Discussionsupporting
confidence: 88%
“…Studies from Canada reported a decrease in children’s outdoor time, which is consistent with our observations. 20 , 21 Children with ASD have a variety of motor impairments, 22 , 23 and the reduction of outdoor exercise time may further aggravate cognitive-motor deficits. In addition, the reduction of outdoor activities also reduce the opportunities for children with ASD to exercise social skills.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, 40.8% of the children in this group were found to be sensitive to movement. Previous studies have documented a range of sensorimotor disorders in ASD, including uncoordinated movements of the upper and lower body, manifesting as difficulty with gait and reaching, respectively ( 29 31 ). Of particular note in this study is the observation that individuals with ASD have difficulty with tasks requiring strong grip strength, lifting heavy objects, and maintaining balance and posture.…”
Section: Discussionmentioning
confidence: 99%